Importance of pulse reversal effect of CdSe thin films for optoelectronic devices - SAAMINATHAN, V; MURALI, K (2005)
Systematic studies of cadmium selenide thin films were prepared by without and with pulse reversal plating technique. In the present work, preparation of CdSe thin films was reported with lower duty cycle and pulse reversal effect. Due to these effects electrical and opto-electronic property of the material were changed. The thin film of CdSe was deposited on cleaned conducting substrates like titanium, SnO2, nickel and stainless steel, respectively. The pulse plated CdSe films without and with pulse reversal films were heat treated and characterized by XRD, optical studies, scanning electron microscopy and photo electrochemical properties. Semiconductor parameters were estimated for without and with pulse plating technique. The barrier height Ob was calculated for CdSe deposited on different conducting substrates. (c) 2005 Elsevier B.V. All rights reserved.